2022
DOI: 10.1002/dta.3354
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between validated GC‐FID and UHPLC‐DAD methods for the analysis of Δ‐9‐THC and CBD in dried hemp flowers

Abstract: Herbal products for smoking containing cannabidiol (CBD) are available as "lowtetrahydrocannabinol cannabis products" in most EU countries. In Belgium, Δ9-tetrahydrocannabinol (THC) content of these products must be less than 0.2% w/w, which is also the limit for agricultural hemp. For agricultural hemp, the official and only valid method for European regulators is gas-chromatography coupled to flame ionization detector (GC-FID). There is no such method, for smoking products.Many of these herbal for smoking pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…A GC-FID method was successfully employed for the detection of seven phytocannabinoids, CBC (1), CBCL (2), CBG (5), CBN (7), Δ 8 -THC (9), THC (10), and tetraydrocannabivarin (THCV, 13) from the researchers. 35,37,39,40,42,51,57,58 A solid-phase-extraction (SPE) method coupled with the GC-FID technique was utilised for the extraction and detection of CBD (3) from C. sativa. Starbons A300 was used as the stationary phase in SPE taking C. sativa extract in n-hexane to selectively adsorb the phytocannabinoids onto the surface, followed by ethanol (EtOH) to facilitate desorption at up to 93%.…”
Section: Gc Analysis Of Phytocannabinoids In Plant Samplesmentioning
confidence: 99%
“…A GC-FID method was successfully employed for the detection of seven phytocannabinoids, CBC (1), CBCL (2), CBG (5), CBN (7), Δ 8 -THC (9), THC (10), and tetraydrocannabivarin (THCV, 13) from the researchers. 35,37,39,40,42,51,57,58 A solid-phase-extraction (SPE) method coupled with the GC-FID technique was utilised for the extraction and detection of CBD (3) from C. sativa. Starbons A300 was used as the stationary phase in SPE taking C. sativa extract in n-hexane to selectively adsorb the phytocannabinoids onto the surface, followed by ethanol (EtOH) to facilitate desorption at up to 93%.…”
Section: Gc Analysis Of Phytocannabinoids In Plant Samplesmentioning
confidence: 99%
“…We appreciate the comments of our colleagues Tsujikawa and Iwata on our article "Discrepancies between validated GC-FID and UHPLC-DAD methods for the analysis of Δ-9-THC and CBD in dried hemp flowers". 1,2 First of all, we were aware that the article could cause some discussion, since it is a very actual topic and most authors suggested liquid chromatography (LC-UV) as the better option for this kind of analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…This is indeed something that was never tested during the validation of the GC-FID method, and therefore, a standard solution of CBDA of 0.2 mg/ml in methanol, corresponding to a herbal sample containing 5% of CBDA, was injected on the GC-FID and analyzed according to the method described in the original article. 2 Figure 1 shows the chromatogram of this analysis, together with a chromatogram of a real sample, found positive for Δ9-THC. As can be seen, no peak was detected at the retention time of Δ9-THC.…”
mentioning
confidence: 91%
See 2 more Smart Citations